EFFECT OF ORGANIC NPK FERTILIZER AND HANTU PLANT GROWTH REGULATOR (PGR) APPLICATION ON GROWTH AND YIELD OF CELERY (Apium graveolus L.) - Indra Kurniawan; Elfin Efendi; Deddy Wahyudin Purba (Universitas Asahan, 2018)
This research was conducted on Durian street, Kisaran Timur, Asahan Regency of North Sumatera Province with flat topography and is at an altitude of 15 m above sea level. The study was conducted from March to May 2017. This research was arranged based on Factorial Randomized Block Design with 2 treatment factors and 3 replications. The first factor is organic NPK with 3 levels: N0 = 0 g/plot, N1 = 25 g/plot, N2 = 50 g/plot. Second factor with PGR Hantuwith 4 levels ie Z0 = 0 ml/l water, Z1 = 1 ml/l water, Z2 = 2 ml/l water, and Z3 = 3 ml/l water. The results showed that organic NPK fertilizer was the best treatment that produced 32,34 cm height, 21,58 pieces of leaves, 65,53 g per plant and 1.75 kg per plot production. The best treatment of PGR Hantu was obtained at a dose of 2 ml/l of water yielding a plant height of 30.99 cm, thenumber of leaves was 21.86 pieces, the production per plant was 67.15 g and the production per plot was 1.78 kg. The interaction between organic NPK fertilizer and PGR Hantu had no significant effect on all observed variables.